2020
DOI: 10.1093/nutrit/nuz107
|View full text |Cite
|
Sign up to set email alerts
|

Portion size estimation in dietary assessment: a systematic review of existing tools, their strengths and limitations

Abstract: Context Overestimation or underestimation of portion size leads to measurement error during dietary assessment. Objective To identify portion size estimation elements (PSEEs) and evaluate their relative efficacy in relation to dietary assessment, and assess the quality of studies validating PSEEs. Data Selection and Extraction Electronic databases, internet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 85 publications
3
52
2
Order By: Relevance
“…A strength in the present validation study is the use of pre-weight foods as the reference tool, which is in line with Amoutzopoulos et al recommendations for validating portion size estimation tools (7) .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A strength in the present validation study is the use of pre-weight foods as the reference tool, which is in line with Amoutzopoulos et al recommendations for validating portion size estimation tools (7) .…”
Section: Discussionsupporting
confidence: 67%
“…Portion size estimates is a critical element in dietary assessment (3–6) . A recent systematic review by Amoutzopoulos et al shows that there is a lack of validated portion size estimation tools, and consequently a pressing need for more validation studies (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portion size estimation is important since misreporting of the consumed amount is a major source of measurement error when assessing dietary intake [44,[48][49][50]. In this study, all apps estimated the amount of food consumed based on the relative portion size entered by users.…”
Section: Portion Size Estimationmentioning
confidence: 99%
“…Future research needs to focus on portion size estimations, which are a major cause of measurement error in most types of dietary assessment 55 . Recent research has suggested that a text‐based description of portion sizes is more accurate than image‐based descriptions 56 ; however, this conflicts with the conclusions of a recent systematic review 57 . This indicates the complexity of portion size estimation, and the need for more research.…”
Section: Discussionmentioning
confidence: 99%